Entropy, Water and Resources An Essay in Natural Sciences-Consistent Economics - Niemes, Horst; Schirmer, Mario; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2010)
This book at the intersection of natural sciences, economics, and water engineering aims to reduce the gaps between economic theory, natural sciences, and engineering practice. Based on an extended thermodynamic approach, the authors explain which economic assumptions are acceptable for constructing a dynamic model that is consistent with the natural sciences. In particular, the special role of water in the production and reproduction activities will be considered as an integral component. Water is generated in a separate water treatment process and is used to transport the unavoidable by-products of production and reproduction activities to a wastewater sector. In this respect, not only environmental protection aspects, but also the interrelation between the water requirements and the use of non-renewable resources for producing desired consumption goods will be highlighted.
The Water Use Model -- Conceptual Foundations: Thermodynamics and Capital Theory -- General Design of Dynamic Models for Water Uses -- Specifications for Constructing the Water Use Model -- Constraints of the Water Use Model -- Optimality Conditions of the Water Use Model -- The Water Infrastructure Model -- Case Studies Guiding the Integration of Water Infrastructure -- Specifications for Constructing the Water Infrastructure Model -- Constraints of the Water Infrastructure Model -- Optimality Conditions of the Water Infrastructure Model.
Keywords: Energy industries; Water pollution; Environmental economics; Economics; Environmental Economics; Energy Economics; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Electronic books